Quizizz-Based Interactive Arabic Learning to Increase the Students' Instruction Interest in Islamic Junior High School at Brebes, Indonesia - Syifani, Ghaida Putri; Madjid, Muh. Naim (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2026)
Abstract This study aims to analyze the effectiveness of the use of Quizizz-based interactive Arabic learning as a medium to increase the students' instruction interest in Islamic junior high school (MTs) at Assalam Salem, Brebes, Indonesia. This study uses a quantitative approach with a one group pretest–posttest design on 34 students selected using purposive sampling techniques. Data was collected through pretest and posttest tests as well as student learning interest questionnaires. The most important result is the normality test showed that the data was not normally distributed (p < 0.05), so the analysis was continued with the Wilcoxon Signed Rank Test. Wilcoxon test data showed a value of Z = −3.993 with a significance of 0.000 (p < 0.05), which indicates a significant difference between the pretest and posttest results. Descriptively, the average score increased from 54.12 to 82.06, and 27 out of 34 students experienced an increase in scores, and the results of the questionnaire showed an increase in students' interest in learning. Thus, it can be concluded that the Quizizz media is effective to be used to increase the students' interest in Arabic learning for the junior high school level.